Faktor Eksternal Industri Pariwisata di Kota Padang dengan Pendekatan Pestel Analysis - Lathif Arafat (Universitas Merdeka Malang, 2018)
The stipulation of tourism as Padang governmental’s vision gives opportunities for business units in tourism industries to grow. However, challenge is where the government of Kota Padang as disaster mitigation. All of this is caused by the dynamical opportunity and threat by external environmental factors. The purpose of this research is to describe (descriptive study) the external environmental factors that affect the tourism industry with PESTEL analysis approach. Data collecting technique is using interviews and literature study. The result of this research is describing the keys success to opportunity factor and to challenge in tourism industry in Padang city with the aspects of politic, economy, sociocultural, technology, environment, and law.